Evolutionary Conservation of Regulatory Elements in Vertebrate Hox Gene Clusters - Santini, Simona; Boore, Jeffrey L.; Meyer, Axel (Genome Research, 2003)
Comparisons of DNA sequences among evolutionarily distantly related genomes permit identification of conserved functional regions in noncoding DNA. Hox genes are highly conserved in vertebrates, occur in clusters, and are uninterrupted by other genes. We aligned (PipMaker) the nucleotide sequences of the HoxA clusters of tilapia, pufferfish, striped bass, zebrafish, horn shark, human, and mouse, which are separated by approximately 500 million years of evolution. In support of our approach, several identified putative regulatory elements known to regulate the expression of Hox genes were recovered. The majority of the newly identified putative regulatory elements contain short fragments that are almost completely conserved and are identical to known binding sites for regulatory proteins (Transfac database). The regulatory intergenic regions located between the genes that are expressed most anteriorly in the embryo are longer and apparently more evolutionarily conserved than those at the other end of Hox clusters. Different presumed regulatory sequences are retained in either the Aα or Aβ duplicated Hox clusters in the fish lineages. This suggests that the conserved elements are involved in different gene regulatory networks and supports the duplication-deletion-complementation model of functional divergence of duplicated genes.
10.1101/gr.700503